Development and utilization of Treponema pallidum expressing green fluorescent protein to study spirochete-host interactions and antibody-mediated clearance: expanding the toolbox for syphilis research - Kristina N. Delgado; Crystal F. Vicente; Christopher M. Hennelly; Farhang Aghakhanian; Jonathan B. Parr; Kevin P. Claffey; Justin D. Radolf; Kelly L. Hawley; Melissa J. Caimano (mBio)
ABSTRACT Syphilis is a sexually transmitted infection caused by the highly invasive and immunoevasive spirochetal pathogen Treponema pallidum subsp. pallidum (TPA). Untreated syphilis can lead to infection of multiple organ systems, including the central nervous system. The alarming increase in syphilis cases globally underscores the importance of developing novel strategies to understand the complexities of syphilis pathogenesis. In this study, we took advantage of recent advances in in vitro cultivation and genetic manipulation of syphilis spirochetes to engineer a TPA strain that constitutively expresses green fluorescent protein (GFP). GFP+ TPA grew identically to the Nichols parent strain in vitro and exhibited wild-type infectivity in the rabbit model. We then used the GFP+ strain to visualize TPA interactions with host cells during co-cultivation in vitro, within infected rabbit testes, and following opsonophagocytosis by murine bone marrow-derived macrophages. The development of fluorescent strain also enabled us to develop a flow cytometric-based assay to assess antibody-mediated damage to the spirochete’s fragile outer membrane (OM), demonstrating dose-dependent growth inhibition and OM disruption in vitro. Notably, we observed greater OM disruption of GFP+ TPA with sera from immune rabbits infected with the TPA Nichols strain compared to sera generated against the genetically distinct SS14 strain. These latter findings highlight the importance of OM protein-specific antibody responses for clearance of TPA during syphilitic infection. The availability of fluorescent TPA strains paves the way for future studies investigating spirochete-host interactions as well as functional characterization of antibodies-directed treponemal OM proteins, the presumptive targets for protective immunity.IMPORTANCESyphilis, a sexually transmitted infection caused by Treponema pallidum (TPA), remains a pressing threat to global public health. TPA has a remarkable and still poorly understood ability to disseminate rapidly from the site of inoculation and establish persistent infection throughout the body. Recent advances in in vitro cultivation and genetic manipulation of syphilis spirochetes enabled the development of fluorescent TPA. In the study, we generated and characterized an infectious TPA strain that constitutively expresses green fluorescent protein and used this strain to visualize the interaction of TPA with host cells and functionally characterize antibodies directed against treponemal outer membrane proteins. Most notably, we assessed the ability of surface-bound antibodies to inhibit the growth of TPA in vitro and/or disrupt the spirochete’s fragile outer membrane. Fluorescent TPA strains provide a powerful new tool for elucidating host-pathogen interactions that enable the syphilis spirochete to establish infection and persistent long-term within its obligate human host.